sw uobaghdad edu iqSynthesis and Characterization of Mn(II), Co(II), Ni(II), Cu(II), Zn(II), and Hg(II) Complexes with Symmetrical Schiff base (Baghdad Science Journal, 2025)
New binuclear Mn(II), Co(II), Ni(II), Cu(II), Zn(II), and Hg(II) Complexes of N2S2 tetradentate or N4S2 hexadentate symmetric Schiff base were prepared by the condensation of butane-1,4-diylbis(2-amino ethylcarbamodithioate) with 3-acetyl pyridine. The complexes having the general formula [M2LCl4] (where L=butane-1,4-diyl bis (2-(z)-1-(pyridine-3-ylethylidene amino))ethyl carbamodithioate, M= Mn(II), Co(II), Ni(II), Cu(II), Zn(II), and Hg(II)), were prepared by the reaction of the mentioned metal salts and the ligand. The resulting binuclear complexes were characterized by molar conductance, magnetic susceptibility ,infrared and electronic spectral measurements. This study indicated that Mn(II), Ni(II) and Cu(II) complexes have octahedral geometry, while Co(II) Zn(II) and Hg(II) complexes are proposed to be tetrahedral structure .K